Synergetic hydrogen-bond network of functionalized graphene and cations for enhanced atmospheric water capture - Xiaojun Ren; Xiao Sui; Amir Karton; Yuta Nishina; Tongxi Lin; Daisuke Asanoma; Llewellyn Owens; Dali Ji; Xinyue Wen; Vanesa Quintano; Komal Tripathi; Kamal K. Pant; et al. (Proceedings of the National Academy of Sciences, 2025)
Water molecules at the solid–liquid interface display intricate behaviors sensitive to small changes. The presence of different interfacial components, such as cations or functional groups, shapes the physical and chemical properties of the hydrogen-bond network. Understanding such interfacial hydrogen-bond networks is essential for a large range of applications and scientific questions. To probe the interfacial hydrogen-bond network, atmospheric water capture is a powerful tool. Here, we experimentally observe that a calcium ion on a calcium-intercalated graphene oxide aerogel (Ca-GOA) surface captures 3.2 times more water molecules than in its freestanding state. From experimental Van’t Hoff estimation and density functional theory (DFT) calculations, we uncover the synergistically enhanced hydrogen-bond network of the calcium ion–epoxide complex due to significantly larger polarizations and hydrogen bond enthalpies. This study reveals valuable insights into the interfacial water hydrogen-bond network on functionalized carbon–cation complexed surfaces and potential pathways for future atmospheric water generation technologies.